Evolution vs. creationism : an introduction - Scott, Eugenie Carol, 1945- (Berkeley : University of California Press, 2009)
Presents the scientific evidence for evolution and reasons why it should be taught in schools, provides various religious points of view, and offers insight to the evolution-creationism controversy.
Foreword : The Unmetabolized Darwin / Niles Eldredge -- Foreword to the Second Edition / Judge John E. Jones III -- Science : Truth without Certainty -- Evolution -- Beliefs: Religion, Creationism, and Naturalism -- Before Darwin to the Twentieth Century -- Eliminating Evolution, Inventing Creation Science -- Neocreationism -- Testing Intelligent Design and Evidence against -- Evolution in the Courts -- Cosmology, Astronomy, Geology -- Patterns and Processes of Biological Evolution -- Legal Issues -- Educational Issues -- Issues Concerning Religion -- The Nature of Science -- Evolution and Creationism in the Media and Public Opinion.
Includes bibliographical references and index.
Keywords: Evolution (Biology); Creationism